The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/s1677-5538.ibju.2022.0587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on size and composition of urinary stones: a systematic review and meta-analysis

Abstract: Background Several studies have explored the impact of BMI on size and composition of urinary stones. Because there were controversies, a meta-analysis was necessary to be carried out to provide some evidence of the relationship of BMI and urolithiasis. Materials and Methods PubMed, Medline, Embase, Web of Science databases, and the Cochrane Library were searched up to August 12th 2022 for eligible studies. The urolithiasis patients were summarized into two groups: BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Moreover, an increased risk of calcium oxalate stone formation was observed in the excess weight group across all patients. Conversely, in this meta-analysis, no significant association between BMI and calcium phosphate was indicated [ 105 ].…”
Section: Disease Influenced By Lifestyle Related To Kidney Stone Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, an increased risk of calcium oxalate stone formation was observed in the excess weight group across all patients. Conversely, in this meta-analysis, no significant association between BMI and calcium phosphate was indicated [ 105 ].…”
Section: Disease Influenced By Lifestyle Related To Kidney Stone Diseasementioning
confidence: 89%
“…While the exact cause of kidney stone disease is still uncertain, individuals with MetS or DM have been found to have higher levels of urinary acidification and production of uric acid stones compared to those without these conditions. Interestingly, as BMI increases in both diabetic and non-diabetic patients, the occurrence of uric acid stones tends to increase while the occurrence of calcium oxalate stones decreases [ 105 , 115 ].…”
Section: Disease Influenced By Lifestyle Related To Kidney Stone Diseasementioning
confidence: 99%
“…Dr. Wang and collegues from China, presented in page 281 ( 1 ) a nice systematic review about the impact of body mass index (BMI) on size and composition of urinary stones and concluded that the current evidence suggests a positive association between BMI and uric acid and calcium oxalate stones. It would be of great guiding significance to con- sider losing weight when treating and preventing urinary stones.…”
mentioning
confidence: 99%